Development and validation of screen dependency scale (SDS) among pre-school children - Abdul Hadi, Azwanis; Roslan, Siti Ruziana; Mohammad Aidid, Edre; Abdullah, Nurzulaikha (2021)
The AAP recommends young children from the age of 2 to 5 years old to use the screen <1 hour per day; and not to expose children less than 18 to 24 months old to any screen media. Screen dependency is a problem associated with prolonged use of the screen leading to addictive symptoms similar to substance addiction such as loss of control and negative emotions (such as irritability and anxiety) when the screen is not available. Thus, a validated and reliable tool is needed to detect the problem at early age for early intervention.